1969
DOI: 10.1159/000274903
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Responses to Acoustic Stimuli

Abstract: Prenatal tests of hearing are practically of great value in making an early diagnosis of deafness. Attempts were made to develop a relatively simple method of prenatal tests of hearing, and 134 fetuses of the 6th–10th month period of pregnancy were examined by means of this method. Pure tones of frequency 500, 1,000 and 2,000 Hz generated by a conventional audiometer were used as acoustic stimuli. Movements of the fetus as well as changes in the fetal pulse rate occurring during or immediately after the stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
1
7
0
Order By: Relevance
“…Conversely, CD15 immunoreactivity disappeared with the formation of stabilized contacts when visual plasticity ended and physiological parameters indicated established visual function. With respect to the inferior colliculus, the period of (discrete) signs of heterogeneity of CD15 expression precedes the time from which somatic and visceral responses have been provoked by auditory stimulation of human fetuses (Fleischer, 1955;Tanaka and Arayama, 1969;Grimwalde et al, 1971;Goodlin and Schmidt, 1972;Berkson et al, 1974;Birnholtz, 1983).…”
Section: Comparison Between the Chronology Of Known Developmental Evementioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, CD15 immunoreactivity disappeared with the formation of stabilized contacts when visual plasticity ended and physiological parameters indicated established visual function. With respect to the inferior colliculus, the period of (discrete) signs of heterogeneity of CD15 expression precedes the time from which somatic and visceral responses have been provoked by auditory stimulation of human fetuses (Fleischer, 1955;Tanaka and Arayama, 1969;Grimwalde et al, 1971;Goodlin and Schmidt, 1972;Berkson et al, 1974;Birnholtz, 1983).…”
Section: Comparison Between the Chronology Of Known Developmental Evementioning
confidence: 99%
“…6, some data regarding parameters of functional maturation of the auditory system are collected. The development of visceral and somatomotor responses that can be registered after abdominal acoustic stimulation depends on the frequencies applied (Fleischer, 1955;Tanaka and Arayama, 1969;Grimwalde et al, 1971;Goodlin and Schmidt, 1972;Berkson et al, 1974;Birnholtz, 1983). Investigations of behavioral responses to pure tone stimuli showed that the first response can be observed at 19 weeks and that, at about 27 weeks, almost all fetuses respond to frequencies up to 1,000 Hz (Hepper and Shahidullah, 1994).…”
Section: Phases Of Intense Neuropil Labeling and (Putative Establishmmentioning
confidence: 99%
“…The foetal sound environment. The first series of human intraabdominal recordings was performed using microphones covered with rubber membranes which were (i) vaginally inserted close to the uterus in either pregnant (Bench, 1968, Murooka, Koie & Suda, 1976 or non-pregnant women , Tanaka & Arayama 1969, Busnel, 1979, or (ii) inside the amniotic cavity after rupture of the membranes during or after delivery , Murooka, Koie & Suda, 1976, Johansson, Wedenberg & Westin, 1964, Henshall, 1972. Except for the acoustic band analysis of Murooka et al (1967) and Busnel (1979), only global measures were performed in these studies.…”
Section: Potential Sources Of Stimulationmentioning
confidence: 99%
“…Consistent with the hypothesis that CD15 is prominent at sites of cellular interactions, a specific interaction between dendrites and afferents in the central nucleus of the human inferior colliculus has been described at 24 weeks of gestation (Geniec and Morest, 1971). With respect to the inferior colliculus, the period of (discrete) signs of heterogeneity of CD15 expression precedes the time from which somatic and visceral responses have been provoked by auditory stimulation of human fetuses (Fleischer, 1955;Tanaka and Arayama, 1969;Grimwalde et al, 1971;Goodlin and Schmidt, 1972;Berkson et al, 1974;Birnholtz, 1983). It remains to be determined whether the heterogeneous CD15 ϩ bands with a similar arrangement correspond to segregated laminae with functional tonotopic organization.…”
Section: Comparison Between the Chronology Of Known Developmental Evementioning
confidence: 99%